2022
DOI: 10.1186/s12948-022-00172-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of oligomerization on the allergenicity of allergens

Abstract: Type I hypersensitivity (allergic reaction) is an unsuitable or overreactive immune response to an allergen due to cross-link immunoglobulin E (IgE) antibodies bound to its high-affinity IgE receptors (FcεRIs) on effector cells. It is needless to say that at least two epitopes on allergens are required to the successful and effective cross-linking. There are some reports pointing to small proteins with only one IgE epitope could cross-link FcεRI-bound IgE through homo-oligomerization which provides two same Ig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 62 publications
1
10
0
Order By: Relevance
“…Ligand binding may also induce the formation of multimeric lipocalin complexes ( 104 ). The dimerization of lipocalin allergens and secrectoglobin Fel d 1 likely impacts their allergenic features and stability ( 105 , 106 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ligand binding may also induce the formation of multimeric lipocalin complexes ( 104 ). The dimerization of lipocalin allergens and secrectoglobin Fel d 1 likely impacts their allergenic features and stability ( 105 , 106 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some evidence indicates that the oligomerization of Alt a 1 is an essential prerequisite for its allergenic potential. Indeed, it has been observed that cross-linking of at least two FcεRI-linked IgE by an allergen is required for mast cell and basophil degranulation [ 43 ]. So, allergen concentration is a key factor in the dimerization of monomeric allergens.…”
Section: Discussionmentioning
confidence: 99%
“…Aggregation and adsorption to natural or anthropogenic particles can also lead to the display of multiple epitopes ( 10 ). In addition to repetitive epitope presentation, nitration and dityrosine cross-linking can lead to epitope modification or shielding, or neoepitope formation ( 8 , 10 , 78 , 81 , 82 ).…”
Section: Nitration and Dityrosine Cross-linking Increase Allergenicit...mentioning
confidence: 99%